2020
DOI: 10.1111/jvim.15747
|View full text |Cite
|
Sign up to set email alerts
|

Blood glucose and insulin concentrations after alpha‐2‐agonists administration in horses with and without insulin dysregulation

Abstract: Background In metabolically stable horses, alpha‐2‐agonists suppress insulin secretion with transient hyperglycemia and rebound hyperinsulinemia. In horses with insulin dysregulation (ID), the effect of alpha‐2‐agonists has not been investigated; however, both the alpha‐2‐agonist‐induced suppression of insulin secretion and rebound hyperinsulinemia could have clinical relevance. Hypothesis/Objectives In horses with ID, alpha‐2‐agonists will alter insulin and glucose dynamics. Animals Seven horses with ID and 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Equine ID is described as a complex metabolic disorder, consisting of both peripheral tissue insulin resistance and hyperinsulinemia (basal or post-prandial), with hyperinsulinemia being associated with laminitis development [ 10 ]. Similar to that which has been described for PPID, previous studies have demonstrated how insulin sensitivity varies with environmental and pathological factors, such as seasonal changes, stress, age, genetics, diet, obesity and systemic disease, but limited data are available regarding the physiological role of internal factors [ 11 , 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 76%
“…Equine ID is described as a complex metabolic disorder, consisting of both peripheral tissue insulin resistance and hyperinsulinemia (basal or post-prandial), with hyperinsulinemia being associated with laminitis development [ 10 ]. Similar to that which has been described for PPID, previous studies have demonstrated how insulin sensitivity varies with environmental and pathological factors, such as seasonal changes, stress, age, genetics, diet, obesity and systemic disease, but limited data are available regarding the physiological role of internal factors [ 11 , 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 76%
“…Both hyperglycaemia and insulin deficiency can cause hyperkalaemia by cellular water loss and decreased cellular uptake of potassium, respectively, 22 which has been documented in human medicine 39 . Xylazine as both a bolus and continuous rate infusion as used in the case presented causes hyperglycaemia in horses, 40‐42 however, these studies did not document concurrent hyperkalaemia. Perioperative hyperglycaemia was documented in the present case, and further glucose was administered after asystole as an emergency treatment for hyperkalaemia alongside insulin, which may or may not have been the correct approach given the hyperglycaemia.…”
Section: Discussionmentioning
confidence: 94%
“…The lungs of the horse were ventilated throughout the anaesthetic (HorseVent; 6-8 bpm; tidal volume 15 ml/kg; peak inspiratory pressure 22-30 cmH 2 O; positive end-expiratory pressure 3-5 cmH 2 O; to maintain normocapnia [EtCO 2 [35][36][37][38][39][40][41][42][43][44][45]). Continuous rate infusions (CRIs) of ketamine (1.2 mg/kg/h), midazolam (0.02 mg/ kg/h) and xylazine (0.3 mg/kg/h) were infused IV combined as a triple drip in one CRI as per the hospital protocol.…”
Section: Anae S the Tic Manag Ementmentioning
confidence: 99%
“…It has been shown in horses that season (β-cell sensitivity), circadian rhythm, diet (structural carbohydrate content), fasting, stress, α 2 -adrenergic agonists and pregnancy could influence endocrine variable and response to dynamic tests. 28,30,38,[40][41][42] Since all baseline samples for the inclusion criteria were collected in the morning in early July, all dynamic tests were performed in the last 2 weeks of July, all animals were kept in the same facility under a feeding protocol similar to the farm of origin, stress was reduced and no treatments were administered; these factors could be discarded.…”
Section: Ta B L E 3 Pearson Correlation Coefficients (R) Among Restin...mentioning
confidence: 99%